2001
DOI: 10.1051/0004-6361:20010354
|View full text |Cite
|
Sign up to set email alerts
|

CI and CO in the spiral galaxies NGC 6946 and M 83

Abstract: Abstract. We present J = 2-1, J = 3-2, J = 4-3 12 CO and 492 GHz [CI] maps as well as J = 2-1 and J = 3-2 13 CO measurements of the late type spiral galaxies NGC 6946 and M 83 (NGC 5236). Both galaxies contain a pronounced molecular gas concentration in rapid solid-body rotation within a few hundred parsec from their nucleus. NGC 6946 and M 83 have nearly identical relative intensities in the 12 CO, 13 CO and [CI] transitions, but very different [CII] intensities, illustrating the need for caution in interpr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
89
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 44 publications
24
89
1
Order By: Relevance
“…For those galaxies that were not mapped in [CI], we have used the J = 4-3 12 CO maps to estimate the convolved [CI] intensity and the total luminosity by assuming identical [CI] and J = 4-3 12 CO distributions. This was shown to be the case for M 83 and NGC 6946 (Petitpas & Wilson 1998;Israel & Baas 2001), but we have further verified the validity of this assumption for all galaxies that were mapped in both [CI] and J = 4-3 12 CO. Values obtained in this way are given in parentheses in Table 2.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…For those galaxies that were not mapped in [CI], we have used the J = 4-3 12 CO maps to estimate the convolved [CI] intensity and the total luminosity by assuming identical [CI] and J = 4-3 12 CO distributions. This was shown to be the case for M 83 and NGC 6946 (Petitpas & Wilson 1998;Israel & Baas 2001), but we have further verified the validity of this assumption for all galaxies that were mapped in both [CI] and J = 4-3 12 CO. Values obtained in this way are given in parentheses in Table 2.…”
Section: Resultssupporting
confidence: 76%
“…For half of the galaxy sample, the distribution of [CI] was mapped beyond the central position (cf. (Israel & Baas 2001); the remaining maps will be discussed in forthcoming papers. In the meantime, we have used the information contained in the maps to convolve the fullresolution central [CI] intensities (Col. 4 of Table 2) to [CI] intensities (Col. 5) appropriate to the twice larger beamsize of the J = 2-1 13 CO observations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limits to the validity of this method come from the fact that the weak metallicity dependence used here for X CO is based on CO interferometric measurements, which may underestimate cloud sizes and hence invalidate the used scaling law (Israel & Baas 2001). The metallicity in M 33 however has a scatter at each radius that is larger than the overall observed radial gradient: a stronger metallicity dependence can be considered only if the metallicity at each source location is known.…”
Section: Radially Varying X Comentioning
confidence: 99%
“…Such observations can be performed from high altitude dry mountain sites, such as the Mauna Kea summit in Hawaii. Previous studies using the James Clerk Maxwell Telescope (JCMT) and the CSO have shown that the 12 CO(4−3) line is generally bright in galaxy nuclei (Guesten et al 1993;Israel et al 1995;Israel & Baas 2001Kramer et al 2005, ...). Much less information is available on the other high frequency CO lines.…”
Section: Introductionmentioning
confidence: 99%